An Expert System for Diagnosing the Impact of Traffic Accidents using the Forward Chaining Method - Akbar Maulana Yusuf; Jonathan Indra Chelidivano; Tavany Amalia Rizky; Yanuar Sabikhi; Sudianto Sudianto (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2023)
Unexpected events that we often hear about are traffic accidents caused by many factors. Accidents also cause impacts in terms of health. This study aims to provide information regarding the effects of traffic accidents in terms of health based on some visible symptoms that emerged from the victim's body at the scene using an expert system. The Expert System is designed on a website-based application. The forward chaining method is used to get a conclusion based on the facts. The results of this research users gain knowledge about the impact of traffic accidents and the diagnosis on the victim's body that is close to the knowledge of experts with accuracy 87.5%. The website is designed to be used as a guide for users to be able to provide appropriate first aid to accident victims.